Contact fracture test of monolithic hybrid ceramics on different substrates for bruxism. Issue 1 (January 2022) - Lan, Ting-Hsun; Chen, Ping-Ho; Fok, Alex Siu Lun; Chen, Yu-Feng
Highlights: Fracture resistance of PICN VE was positively associated with specimen thicknesses. 0.8 mm PICN VE on stiff substrate could withstand static heavy force 800 N loading. 2.0 mm PICN VE on stiff substrate could withstand 800 N sliding motion. PICN VE on soft substrate was not recommended for clinical use in bruxism. Abstract: Objectives: To determine the minimum thickness required for a monolithic hybrid ceramic crown on different substrates (soft vs stiff) used in posterior dentition for bruxism. Methods: 80 polymer-infiltrated ceramic networks Vita Enamic (PICN VE) disc specimens with four different occlusal thicknesses (0.8, 1.2, 1.6 and 2.0 mm), were produced using a computer-aided design/manufacturing system, and cemented on a stiff (zirconia) or soft (polyamide) substrate of 4-mm thickness. The ten specimens, in soft or stiff groups, were subjected to compressive loading by a MTS machine until fracture or maximum load (4500 N) was reached. The unbroken specimens were examined using optical coherence tomography. Eight axisymmetric finite element models and eight 3D models comprising the four different occlusal thicknesses and two substrates under different vertical loads and sliding movements were constructed. The maximum principal stress was selected to evaluate the stress distribution in this study. Results: The fracture resistance of the specimens was significantly different between the two substrates (P < 0.001). Fracture resistance was positively associated with specimen thickness ( r = 0.597 and 0.896 for the soft and stiff substrate respectively). Specimens on the soft substrate had lower fracture loads, whilst cone cracks were observed in unbroken samples on different soft/stiff substrate prior to final fracture. The finite element analysis confirmed that samples on the stiff substrate had lower maximum principal stress values than those on the soft substrate. For the maximum principal stress not to exceed the flexural strength of PICN VE, a stiff substrate and minimum thickness of 2.0 mm are required for the prostheses. Significance: A minimum 2.0 mm thick, stiff substrate was needed for bruxism as shown by the effect of high/large chewing force on the posterior dentition of monolithic PICN VE crowns.